Implementasi Lampu Penerangan Taman Otomatis Menggunakan Mikrokontroler Berbasis IoT (Studi Kasus Taman Perumahan Maharaja Depok) - Aldian Mahmud; Weni Gurita Aedi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The development of science and technology has a positive impact on human life, which at this time has reached modern times. many innovations from the progress of this era that continue to grow to help facilitate human work. Of the many types of innovation, most of them use microcontrollers in automated systems. With the addition of the Internet Of Things system, we can control and access existing electronic equipment remotely by utilizing an installed internet connection. Lighting of public places such as parks using the control of the esp-8266 microcontroller system is one form of the progress of the era that is heading towards modernity. Lighting public places using a microcontroller is one way to reduce the waste of electrical energy. The method in this study uses an experimental method that produces garden lighting using a microcontroller with several stages of system testing starting with individual component testing, components that are connected to other components, functional system testing and overall system testing. The results obtained from this study are to create an automatic control system, so that the system can control electronic devices automatically, or manually.